Inhibition of cytochrome P450 (CYP3A4) activity by extracts from 57 plants used in traditional Chinese medicine (TCM) - Ashour, Mohamed L.; Youssef, Fadia S.; Wink, Michael (Pharmacognosy magazine, 2017)
Background: Herbal medicine is widely used all over the world for treating various health disorders. It is employed either alone or in combination with synthetic drugs or plants to be more effective. Objective: The assessment of the effect of both water and methanol extracts of 57 widely used plants from Traditional Chinese Medicine (TCM) against the main phase I metabolizing enzyme CYP3A4 in vitro for the first time. Materials and Methods: The inhibition of cytochrome P450 activity was evaluated using a luminescence assay. The principal component analysis (PCA) was used to correlate the inhibitory activity with the main secondary metabolites present in the plant extracts. Molecular modeling studies on CYP3A4 (PDB ID 4NY4) were carried out with 38 major compounds present in the most active plant extracts to validate the observed inhibitory effect. Results: Aqueous extracts of Acacia catechu, Andrographis paniculata, Arctium lappa, Areca catechu, Bupleurum marginatum, Chrysanthemum indicum, Dysosma versipellis, and Spatholobus suberectus inhibited CYP3A4 is more than 85% (at a dose of 100 μg/mL). The corresponding methanol extracts of A. catechu, A. paniculata, A. catechu, Mahonia bealei, and Sanguisorba officinalis inhibited the enzyme by more than 50%. Molecular modeling studies revealed that two polyphenols, namely hesperidin and rutin, revealed the highest fitting scores in the active sites of the CYP3A4 with binding energies equal to -74.09 and -71.34 kcal/mol, respectively. Conclusion: These results provide evidence that many TCM plants can inhibit CYP3A4, which might cause a potential interference with the metabolism of other concomitantly administered herbs or drugs. SUMMARY: In this study, the inhibitory activity of the aqueous and methanol extracts of 57 widely used plants from Traditional Chinese Medicine (TCM) against the main phase I metabolizing enzyme CYP3A4 was tested in vitro for the first time.Aqueous extracts of Acacia catechu, Andrographis paniculata, Arctium lappa, Areca catechu, Bupleurum marginatum, Dysosma versipellis, and Spatholobus suberectus inhibited CYP3A4 by more than 85% (at a dose of 100 μg/mL).The activity could be attributed to the presence of polyphenolics as revealed from the multivariate chemometric analysis and molecular modeling study.These results provide evidence that many TCM plants can inhibit CYP3A4, which might cause a potential interference with the metabolism of other concomitantly administered herbs or drugs. Abbreviation used: CHARMm: Chemistry at HARvard Macromolecular Mechanics, CYP: Cytochrome P450, DMSO: Dimethyl Sulfoxide, PCA: Principal Component Analysis, PDB: Protein Data Bank, TCM: Traditional Chinese Medicine